Chemical bonding and optical bowing in III-nitrides solid solutions - Voznyy, O.V.; Deibuk, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Chemical bonding and electronic properties of III-nitrides solid solutions are studied using a model empirical pseudopotential method in modified virtual crystal approximation taking into account positional and compositional disorder. The changes in chemical bonding are analyzed in different ionicity models. The bowing is mainly caused by compositional disorder, volume deformation effects and valence charge redistribution in the alloys. The connection between the value of the bowing and basic parameters of the materials is found.